UPAYA GURU DALAM MENINGKATKAN MINAT BACA SISWA DI MADRASAH IBTIDAIYAH RAUDLATUL ULUM MALANG - Farda Nurmawati; Rosichin Mansur; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Reading interest is encouragement to understand word for word and fill the reading contained in the text, so that the reader can make sense of things put into a reading. To raise reading interest students and a teacher and a librarian have to reading interest exemplary against high to give students in a school. This research is the kind of research largely qualitative case study. Data collection techniques to observation activities or observation, deep interview and documentation. The results of research efforts to teachers raise reading interest students have well done but reading interest of students still low in the category, it is suspected that this because of the lack of support from the environment and parents when it takes place at home. So that students only to receive from teachers alone, and it will not be enough to stimulate reading interest among students. While in reality the aspect of the family, the community, and educaional institutions have significant roles in increasing peoples interest in reading. All these aspects must be related and carried out in stages to get maximum results to improve student reading interest.Keywords: Student interest in reading, Efforts to master.